Pengaruh E-Service Quality dan Online Customer Review Terhadap Keputusan Pembelian Jasa Kamar Menggunakan Online Travel Agent di Hotel Pangeran Beach:Peran Customer Trust Sebagai Mediasi - Kheir, Zuhra Riadatul; Abrian, Youmil (CV. ITTC INDONESIA, 2024)
This study examines how e-service quality and online customer reviews influence the decision to purchase rooms at Pangeran Beach Hotel through online travel agents, with customer trust serving as a mediating variable. The objective of this study is to empirically assess the direct and indirect impacts of both independent factors on the dependent variable at Hotel Pangeran Beach. This study employs a quantitative method utilizing structural equation modeling (SEM) and a selective sampling strategy to examine data from 180 hotel guest respondents. The investigation results revealed that both e-service quality and online customer reviews have a significant impact on the decision to purchase rooms at Pangeran Beach Hotel, both directly and indirectly, or partially through Customer Trust. These findings have practical implications, including the need for better service quality and effectiveness.